Systematic review for comparision of metoprolol succinate vs metoprolol tartrate or carvedilol in: primary hypertension, congestive heart disease and ischemic heart disease treatment - Kawalec, Paweł; Borek, Ewa; Szczuka, Anna (Przewodnik Lekarza/Guide for GPs, 2006)
Background: Beta-receptor blocking drugs (including metoprolol succinate; metoprolol CR/XL; Betaloc ZOC) are among the most frequently used drugs in cardiology (mostly in prevention of cardiac events, in hypertension treatment as well as in congestive heart disease). The basic aim of the analysis was assessment of clinical effectiveness of metoprolol succinate treatment in patients with congestive heart failure, primary hypertension and coronary heart disease compared to metoprolol tartrate and carvedilol. Methods: Clinical assessment was performed according to Cochrane Collaboration criteria; analysis and credibility evaluation was based on evidence-based medicine. A systematic review of medical databases (Medline, Cochrane, Embase) was performed to find relevant clinical publications. Results: Systematic review revealed 6 relevant ”head-to-head comparison” clinical trials, which made it possible to compare clinical effectiveness and safety of metoprolol succinate and metoprolol tartrate or carvedilol in hypertension treatment; 4 publications on metoprolol succiante vs metoprolol tartrate or carvedilol were found referring to coronary heart disease and 11 publications on clinical effectiveness of the drugs in congestive heart disease. Meta-analysis of the trials revealed a statistically significant difference in blood pressure normalization in 69.2% and 63.4% of patients treated with metoprolol succinate and metoprolol tartrate respectively; safety profile was significantly better for Betaloc Zoc compared to metoprolol tartrate. Treatment of hypertension with Betaloc Zoc was also significantly more effective compared to caverdilol (74.1% vs 81%). Merit and Copernicus clinical trials revealed an insignificant trend favouring Betaloc ZOC compared to carvedilol in reduction of probability of cardiac events in patients with congestive heart disease. In patients with coronary heart disease treated with metoprolol succinate the risk of cardiac pain was significantly lower than in patients on carvedilol (relative risk reduction was 0.42). Conclusions: Metoprolol succinate is a superior treatment option compared to metoprolol tartrate or carvedilol in treatment of hypertension, congestive heart disease and coronary heart disease.